Integrating process writing approach with scaffolding strategies in developing esl writing skill: Towards a pedagogical model - Wardatul Akmam, Din (2016)
There has been growing evidence that the lack of academic writing skill among university students who learn English as a Second Language (ESL) affects their overall academic performance. Higher education ESL students often find writing academic essays a complex process and hence struggle with academic writing convention issues. Using the lenses of Explanatory Sequential Mixed Methods, this two-phase study aimed to investigate the students’ behaviours and the reasons behind their academic writing problems. In the first phase of the research, quantitative data from questionnaire responses of 1800 undergraduates were interpreted and the experiences and practices of successful and non-successful Malaysian undergraduate writers were gathered and analysed to elicit the Malaysian ESL students’ behaviours during writing engagement. The second phase of the research involved a teaching intervention of ESL Academic Writing. Good writing practices identified in the first part of the research were woven together and scaffolded with the Process Writing Approach, essay models, language input and knowledge on the conventions of academic writing. The intervention module was utilized with 30 MUET band 1 and 2 undergraduates for 14 weeks. Findings employing Structural Equation Modelling approaches indicated that writing attitude, writing behaviour, and writing difficulties do collectively explain the variance in the students’ MUET results. Findings of the second phase of the research from the analysis of the pre-test, post-test, delayed post-test, students’ writing samples and diaries, indicated that the scaffolded process approach was successful in encouraging the students to adopt writing strategies, reducing the number of Surface Level Revisions and significantly increasing their Meaning Preserving Revisions. Besides informing scholarly practices of academic writing, this research would contribute to the field of ESL Academic Writing as it highlights the crucial elements that need to be incorporated in an effective ESL Academic Writing module at Malaysian higher education institutions.